DETERMINATION OF FREE ACIDITY IN SULFURIC LIQUORS USING THE OXALATE METHOD: SCOPE, LIMITATIONS, AND VALIDATION (REMUNOM, 2025)
The Oxalate Method is a classical procedure for determining free acidity in complex sulfuric liquors from hydrometallurgical processes. By selectively complexing hydrolysable cations such as Fe³⁺, Al³⁺, and Mg²⁺ through the addition of potassium oxalate, the method reduces interference from metal hydrolysis. This revised study incorporates reviewer feedback, including discussion of chemical mechanisms, industrial applications, and the effects of interfering ions. The method demonstrated robust performance up to 40 g/L of Fe³⁺ and across a wide acidity range, making it suitable for routine monitoring of leaching solutions containing elevated levels of base metals. Additionally, an adaptation for low-acidity samples is proposed, improving their analytical applicability in diluted matrices.